Weekly Press Release of Istanbul Gelisim University (Issue 174) (21-25 November 2022) - İstanbul Gelişim Üniversitesi Rektörlüğü (İstanbul Gelişim Üniversitesi / Istanbul Gelisim University, 2022)
IGU FACULTY OF DENTISTRY “2022-2023 ACADEMIC YEAR WHITE COAT CEREMONY” WAS HELD Istanbul Gelisim University (IGU) Faculty of Dentistry organized the “2022-2023 Academic Year White Coat Ceremony” for students who have just started the faculty this year. The ceremony, which started with a moment of silence and the National Anthem, continued with the speeches of Chairman of the Board of Trustees Abdulkadir Gayretli, Rector Prof. Dr. Bahri Sahin, Dean of the Faculty of Dentistry Prof. Dr. Mahir Gunday and President of the Istanbul Chamber of Dentists Prof. Dr. Sertac Peker. After the opening speeches, Soner Can Dinler gave a violin concert. https://gelisim.edu.tr/en/news/igu-faculty-of-dentistry-%E2%80%9C2022-2023-academic-year-white-coat-ceremony%E2%80%9D-was-held
Keywords: Istanbul Gelisim University; Bulletins; Weekly Bulletins